Inherently nitric oxide containing polymersomes remotely regulated by NIR for improving multi-modal therapy on drug resistant cancer. (October 2021) - Liu, Zhihong; Zhong, Yinan; Zhou, Xiang; Huang, Xin; Zhou, Jingjing; Huang, Dechun; Li, Yanfei; Wang, Zhixiang; Dong, Bin; Qiao, Haishi; Chen, Wei
Abstract: The therapeutic potential of nitric oxide (NO) has been highly attractive to tumor treatment, especially for surmounting the multidrug resistance (MDR) of cancer. However, the NO-involved therapy remains extremely challenging because of the difficulty to simultaneously control the NO release rate and real-time concentration. Herein, we construct NO-containing polymersomes with high amount of NO donors inherently grown on the polymer chains to keep the stability. These polymersomes can be simultaneously loaded with photosensitizer of IR780 iodide on the membrane layer and chemotherapeutic of DOX·HCl in the lumen. NO release can be triggered by the reduction conditions, and further accelerated by remote NIR irradiation due to the increased local temperature. The instantaneous NO release with high concentration significantly inhibits the P-gp expression and sensitize the chemotherapy, thus overcoming the tumor MDR and improving the anti-tumor activity. Meanwhile, DOX·HCl release is highly promoted at the intracellular conditions because of the cleavage of acid-labile cis -aconitic amide at endo/lysosomal pH, and the improved hydrophilicity of the membrane layer after NO release. The in vivo results show that the single intravenous injection of polymersome formulation companying with NIR irradiation exerts multi-modal therapies of chemotherapy, PTT/PDT, and NO-therapy on the MCF-7/R tumor models, showing superior and combinational treatment efficacy with the complete eradication of tumors and few side effects.